2017
DOI: 10.1016/j.eats.2016.09.023
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic Technique for Treatment of Schatzker Type III Tibia Plateau Fractures Without Fluoroscopy

Abstract: Accurate reduction and maintenance of the stability with correct implant positioning is critical for surgical treatment of tibial plateau fractures. Our technique includes an arthroscopic reduction and fixation of Schatzker type III tibial plateau fractures with a bulls-eye screw placement without fluoroscopy control. With the arthroscopic guidance, an anterior cruciate ligament drill guide is placed and a K-wire sent to the midpoint of the depressed fragment through the guide at a 40 angle to the coronal axis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…Some specific features differentiate our technique from other arthroscopic procedures. First, most of them require drilling a canal in the proximal tibia and using a K-wire, a bone tamp, or an inflatable balloon for fracture reduction and correction of the articular depression of the posterolateral tibial plateau 3, 6, 7, 8. This technique makes the fracture reduction possible only when the special anterior cruciate ligament aiming guide is available and has a risk of iatrogenic articular cartilage lesions and displacement of the fracture fragment into the joint 11 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some specific features differentiate our technique from other arthroscopic procedures. First, most of them require drilling a canal in the proximal tibia and using a K-wire, a bone tamp, or an inflatable balloon for fracture reduction and correction of the articular depression of the posterolateral tibial plateau 3, 6, 7, 8. This technique makes the fracture reduction possible only when the special anterior cruciate ligament aiming guide is available and has a risk of iatrogenic articular cartilage lesions and displacement of the fracture fragment into the joint 11 .…”
Section: Discussionmentioning
confidence: 99%
“…Another advantage of the current presented technique is that precise fracture reduction can be achieved without using fluoroscopy, which eliminates the risk of radiation exposure. It is of benefit not only for the patient, but also for the medical staff working in the operating room 8 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many authors have recommended arthroscopyassisted techniques and external fixator applications (3,(15)(16)(17)(18). Each of these techniques has its limitations, such as need for special equipments and experience.…”
Section: Discussionmentioning
confidence: 99%
“…These early studies showed a low incidence of complications and satisfactory clinical and radiological results. (6)(7)(8)(9) A thorough understanding of the clinical and imaging anatomy of the tibial plateau and the tibial plateau is essential when trying to perform less invasive surgery on intraarticular plateau fractures. All these new technologies have achieved good clinical results.…”
mentioning
confidence: 99%